Effect of Workplace Spirituality on Quality of Work Life of Nurse Cancer Survivors in South Korea - Jin, Juhyun (Asia Pac J Oncol Nurs, 2020)
OBJECTIVE: Return to work is known to have a positive effect on the quality of work life of cancer survivors, including the nurse cancer survivors, along with other factors, such as workplace spirituality. The aim of this study was to identify the effect of workplace spirituality and its constituent concepts on the quality of work life of nurse cancer survivors. METHODS: A cross-sectional survey comprising the nursing workplace spirituality (NWS) and quality of nursing work life (QNWL) scales was completed by 130 cancer survivor nurses between October 15, 2018, and May 15, 2019, in two general hospitals in metropolitan areas, and snowball sampling was used in parallel. The data were analyzed using SPSS 22 software, determining descriptive statistics, and conducting an independent t-test, one-way ANOVA, Pearson's correlation coefficient, and hierarchical multiple regression. RESULTS: The average scores for all NWS and QNWL subdomains were medium. Age, nursing tenure, and the factors of NWS were positively correlated with QNWL, especially the harmony between the workplace and the individual (r = 0.65, P < 0. 001). In the second hierarchical regression, controlling general characteristics, harmony between the workplace and the individual (β = 0.38, P ≤ 0.001), and relationship with colleagues (β = 0.19, P = 0.031) were significant predictors of QNWL explaining 59.0% of the variance. This model was found to be suitable (F = 16.29, P ≤ 0.001). CONCLUSIONS: Effective and practical organizational systems and intervention programs based on organizational support, including colleagues' support for increasing the quality of work life for nurse cancer survivors, are required.